O planejamento didático no retorno das aulas presenciais em uma escola pública de Parintins-AM em tempos de pandemia da Covid-19 - Castro, Elizandra de Oliveira (Brasil, 2023)
This study aims to investigate how Didactic Planning took place in the early years of elementary school in the return of face-to-face classes in a public school in Parintins in times of the Covid- 19 Pandemic. It was also proposed to identify the main concerns and preparation of teachers regarding the return to face-to-face classes, describe how the didactic planning was elaborated by the teachers and present their difficulties and strategies used in the elaboration of the didactic planning for the return of face-to-face classes. This research took a qualitative approach and was carried out in a school in the municipal network of Parintins-AM, with a group of four teachers who teach classes in the early years of elementary school (1st to 5th) as interviewed subjects. In the production of data, a semi-structured interview was used. The results show that with the Covid-19 pandemic, there was a very large delay in the educational process of children, since a majority did not have the opportunity to follow online classes, as they did not have access to technological tools and quality internet. This issue also made it difficult for teachers to elaborate didactic planning. Teachers were not one hundred percent prepared for this return, they would still have to deal with student difficulties. However, little by little, they overcame obstacles as they sought new ways of teaching, creating new learning possibilities.